Recurrent carbon footprint assessment and forecasting for conventional housing in tropical regions: A Malaysian case study - Shafiq, N. (John Wiley and Sons Inc., 2018)
Almost all life cycle assessment methods of carbon footprint for conventional housing in tropical region have either ignored the impacts of recurrent carbon or considered based on random assumptions. To ensure the green and sustainable urban built environment, particularly in tropical regions, an accurate monitoring and control of carbon footprint requires a comprehensive assessment of all phases of project life cycle, including maintenance. This article presents an innovative and dynamic approach of forecasting of carbon footprint including the recurrent carbon by combining a statistical (simple and multiple regression) and simulation (3D parametric prototyping) technique in a partial LCA (cradle to site) study for a tropical built environment. The developed multivariable regression model satisfied the statistical criteria of an efficient and consistent tool as the average percentage error of the predicted and observed values was found within the acceptable range. The average contribution of CO2 ranged from 2.0 tons to 40 tons for 25 to 100 year of service life span. Ceramic tiles, false ceiling, plaster and roof tiles remained the top materials. The model validation observed an acceptable average error range from (â) 3.24 to (+) 8. The study analyzed the factual recurrent carbon footprint impacts and justified the importance of its inclusion in preemptive mitigation toward sustainability concerns at very early stage of the housing project. Â© 2017 American Institute of Chemical Engineers Environ Prog, 37: 839â849, 2018. Â© 2017 American Institute of Chemical Engineers Environ Prog